Descrição de vértebras cervicais de thalassodrominae (Pterosauria, Pterodactyloidea) - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Although various specific characters are known and used in pterosaur vertebrae identification, the cervical series is still poorly studied. In order to enhance the knowledge regarding Tapejaridae vertebrae, we describe three cervical vertebrae belonging to a pterosaur identified by cranial elements as Tupuxuara sp., from the Araripe Basin and showcasing excellent preservation. The material is comprised of the first atlas-axis described for Thalassodrominae, along with the two subsequent cervical vertebrae. Although they belong to a sister subfamily, vertebrae IV presents characters previously reported as diagnostic for Tapejarinae, such as the presence of a single lateral foramen and concave ventral surface. New characteristics for the gamily are described as well, such as the lack of pneumatic foramina on vertebrae III.
Description of thalassodrominae (Pterosauria, Pterodactyloidea) cervical vertebrae
Keywords: Tapejaridae; Bacia do Araripe; Thalassodrominae; Tupuxuara; Talassofrinídeo; Araripe Basin; CNPQ::CIENCIAS BIOLOGICAS